2022
DOI: 10.1108/md-07-2021-0993
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility and firm value: evidence from Chinese targeted poverty alleviation

Abstract: PurposeWhilst the relationship between corporate social responsibility (CSR) and corporate financial performance has been well documented, CSR has rarely been studied from the perspective of corporate poverty alleviation. This study aims to test whether participation in targeted poverty alleviation (TPA) affects firms' market value and to explore how the magnitudes of market value vary in different CSR environments.Design/methodology/approachBased on recent Chinese TPA initiatives and on 108 TPA announcements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Finally, we focus on the overall performance of corporate ESG strategies. More specific factors concerning ESG in the Chinese context could be discussed in future studies (Huang et al, 2022). For example, future studies could investigate how corporate integrity culture impacts the participation and intensity of poverty alleviation activities.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we focus on the overall performance of corporate ESG strategies. More specific factors concerning ESG in the Chinese context could be discussed in future studies (Huang et al, 2022). For example, future studies could investigate how corporate integrity culture impacts the participation and intensity of poverty alleviation activities.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, from the governance perspective, higher management members are more experienced. Studies have shown that older board members are more inclined to make charitable donations [ 3 , 12 ].…”
Section: Empirical Analysis and Discussionmentioning
confidence: 99%
“…Companies are increasingly expected to adopt socially responsible and sustainable policies and practices, such as fair labor, ethical sourcing, and environmental sustainability. These can reduce the negative impact of business on society and the environment, and support poverty alleviation [ 12 ]. Furthermore, effective internal governance controls can ensure that these social initiatives are well designed, executed, and evaluated to achieve their goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legitimacy is important because once firms are perceived by society as illegitimate, they will have difficulty gaining stakeholder support [48]. Conversely, organizations that are perceived as legitimate are able to access scarce resources from stakeholders such as creditors, suppliers, trade associations, and regulators [49]. Therefore, to enhance their likelihood of survival and growth in the marketplace, firms must actively take effective measures to change stakeholders' perceptions of their behavior in order to seek or maintain legitimacy [14].…”
Section: Hypothesis Development 221 Legitimacy Theorymentioning
confidence: 99%